The Stability of Glutardialdehyde-Stabilized 35-Heparinized Surfaces in Contact with Blood - Larsson, R. L; Hjelte, M.-B; Eriksson, J. C; Lagergren, H. R; Olsson, P (Thrombosis and Haemostasis, 1977)
Heparin can be bound to polymer surfaces by precipitation of an ionic heparin-amine complex which can be stabilized against dissolution by treatment with glutardialdehyde. The aim of this investigation was to study the degree and course of desorption of heparin from such a heparinized surface on contact with blood. This desorption must be considered when analysing the interaction between the heparinized surface and blood. Different heparinized surfaces were prepared by using 35S-labelled heparin, and the desorption of heparin on exposure in vitro to citrated plasma or heparinized blood as well as during exposure at in vivo conditions was quantified.During in vitro experiments, the glutardialdehyde stabilized surface became stable with no further desorption of heparin after an initial loss of about 3% of the initial surface-bound heparin. Under in vivo conditions, there was an initial loss of about 12%. There was no further loss from surfaces inserted into the circulation of the dog for seven days as compared to those inserted for one hour.